On pluralism, religious ‘other’, and the Quran: a post September-11 discourse - Mohd Yaseen Gada (IAIN Salatiga, 2016)
The plurality and diversity of religions is not a new thing that we experience in the postmodern world. History is testimony to the fact that different religions have evolved and existed on the face of earth as the human life moved forward. However, in the recent decade, particularly aftermath of 9/11, the bourgeoning conflict, violence, hatred pervasive in the world is often attributed to different ideologies and values associated with religions, Islam with no exception. Therefore, Muslims living as minorities on the both sides of the Atlantic Ocean are in a precarious condition. Besides, the increasing proximity between the individuals of different religions and, more so, of communities due to the miraculous advancements in the technology of communication and transport facilities have resulted into inevitable intercultural interaction and integration more than ever before. Consequently, attempts are being made to explain Islam’s compatibility with Western concept of religious pluralism. Islam recognises political, social pluralism rather than religious pluralism per se, which are explicit in the Quran and the prophetic traditions.I n this background, the paper is an attempt to re-explore and re-revisit the concept of pluralism in Islamic sources. It attempts to re-construct the theme of pluralism away from the extremes to a balanced (wasatiyya) and viable one that strives for the recognition and accommodation of the religious “other” without nullifying Islam’s own essence and identity. The paper concludes that Islam not only recognizes, appreciates and tolerates the religious differences but it also demands for peaceful coexistence and mutual understanding among different religions. Pluralitas dan keragaman agama bukan hal baru yang kita alami dalam dunia postmodern. Sejarah adalah kesaksian fakta bahwa agama-agama yang berbeda telah berevolusi dan ada di muka bumi sebagai kehidupan manusia bergerak maju. Namun, dalam dekade terakhir, khususnya setelah 9/11, konflik, kekerasan, kebencian yang menyebar di dunia ini sering dikaitkan dengan ideologi yang berbeda dan nilai-nilai yang berhubungan dengan agama, Islam tanpa terkecuali. Oleh karena itu, umat Islam yang hidup sebagai minoritas di kedua sisi Samudra Atlantik berada dalam kondisi genting. Selain itu, kedekatan kian meningkat antara individu-individu dari berbagai agama dan, lebih dari itu, masyarakat karena kemajuan ajaib dalam teknologi komunikasi dan fasilitas transportasi telah mengakibatkan interaksi antarbudaya yang tak terelakkan dan integrasi yang lebih dari sebelumnya. Akibatnya, diperlukan upaya yang untuk menjelaskan kompatibilitas Islam dengan konsep Barat mengenai pluralisme agama. Islam mengakui, pluralisme sosial politik daripada pluralisme agama per se, yang eksplisit dalam al-Quran dan tradisi kenabian. Dalam latar belakang ini, kajian ini merupakan upaya untuk kembali mengeksplorasi dan meninjau kembali konsep pluralisme dalam sumber-sumber Islam. Kajian juga mencoba untuk membangun kembali tema pluralisme dari pendekatan yang ekstrem ke pendekatan moderat (wasatiyya) dan berusaha untuk mengakui dan mengakomodasi agama “lain” tanpa meniadakan esensi dan identitas Islam sendiri. Makalah ini menyimpulkan bahwa Islam tidak hanya mengakui, menghargai dan mentoleransi perbedaan agama tetapi juga menuntut untuk hidup berdampingan secara damai dan saling pengertian antara agama-agama yang berbeda.